(untitled) (Third Sector Social Economic Review, 2025)
This study examines the level of financial literacy (FL) and the impact of social media use on FL through a survey conducted among individuals aged 18 and over residing in the province of Samsun. The questionnaire, structured based on the OECD/INFE framework, consists of three main sections: participants’ demographic characteristics, basic financial knowledge levels, and the use of social media for financial purposes. Data collected online from a total of 401 participants were analyzed using the SPSS 21.0 program. The findings indicate that overall FL levels are low; however, they increase significantly with age, education, and income levels. Male participants scored higher than female participants. While the use of credit cards and participation in the private pension system (BES) were found to have a positive effect on FL, the use of internet banking did not result in a statistically significant difference. A weak but statistically significant relationship was identified between social media use and FL. This suggests that while social media may facilitate access to financial information, it may not provide an effective learning environment on its own. The results reveal that FL is not merely a cognitive competence, but also a multidimensional field shaped by experience, attitudes, and behavior. The study highlights the need for locally implemented FL education programs supported by digital content, especially targeting women, youth, and low-income groups. Holistic intervention models developed through the collaboration of municipalities, NGOs, and financial institutions may contribute to enhancing FL at a societal level.